1993
DOI: 10.1093/oxfordjournals.aje.a116911
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors Associated with Cervical Human Papillomavirus Infections: A Case-Control Study

Abstract: As a part of the long-term prospective follow-up study conducted for women with genital human papillomavirus (HPV) infections in Kuopio University Hospital, Finland, since 1981, a case-control study was designed to assess risk factors for genital HPV infections. The cases (n = 691) were women who had been invited to attend the follow-up program on the basis of an abnormal cervical smear consistent with HPV-induced cytopathic changes, i.e., had a clinical HPV infection. The controls (n = 706) were a randomly se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
49
2
5

Year Published

2000
2000
2019
2019

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 87 publications
(62 citation statements)
references
References 0 publications
6
49
2
5
Order By: Relevance
“…Our analyses confirmed the findings of previous studies that demonstrated that age of first sexual intercourse is significantly associated with subsequent HPV infection, [13][14][15][16] but extended previous findings in that we specifically examined which risk behaviors and partner characteristics mediate the association between age of first sexual intercourse and subsequent HPV infection. As previously discussed, a risk behavior or partner characteristic acts as a mediator of the association between age of first sexual intercourse and HPV infection if age of first sexual intercourse is causally associated with the potential mediator and the potential mediator is causally associated with HPV infection.…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…Our analyses confirmed the findings of previous studies that demonstrated that age of first sexual intercourse is significantly associated with subsequent HPV infection, [13][14][15][16] but extended previous findings in that we specifically examined which risk behaviors and partner characteristics mediate the association between age of first sexual intercourse and subsequent HPV infection. As previously discussed, a risk behavior or partner characteristic acts as a mediator of the association between age of first sexual intercourse and HPV infection if age of first sexual intercourse is causally associated with the potential mediator and the potential mediator is causally associated with HPV infection.…”
Section: Discussionsupporting
confidence: 89%
“…A number of studies have demonstrated that sexual risk behaviors are associated with HPV infection, particularly with high oncogenic risk types. These behaviors include multiple 14,15,[32][33][34][35] Other risk behaviors that have been associated with HPV infection include smoking and alcohol use. 14,15 Black race has also been associated with HPV infection.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations